Sequential extraction of saponins from Eurycoma longifolia roots by water extraction and ultrasound-assisted extraction - Elhag, Husam Eldin Elhag Abugabr; Nailaa, Aishath; Azilah, Ajit; Badhrulhisham, Abdul Aziz; Ahmad Ziad, Sulaiman (Elsevier Ltd, 2018)
Central composite designs (CCDs) for UAE and WE were established by seven and five extraction factors, respectively, to determine their optimum conditions that maximized the saponins yields. These optimum conditions were employed successively to establish a sequential extraction (SE) of saponins from Eurycoma longifolia roots. Results identified the agitation speed as an influencing factor in altering the interactive effects of the extraction factors in UAE and WE. Optimized conditions illustrated that higher agitation speeds increased the yields of saponins in WE while UAE preferred lower agitation speed ranges. This implied that the high agitation speeds decreased the collision of microjets and particles and hence the the decrease of sonication efficiency. The SE extraction was proposed by initial sonication of the plant sample for a duration of 5 minutes and 29 seconds to 10 minutes followed by conventional WE for 20-25 minutes.